Does postoperative morbidity worsen the oncological outcome after radical surgery for gastrointestinal cancers? A systematic review of the literature - Shimada, Hideaki; Fukagawa, Takeo; Haga, Yoshio; Oba, Koji (Annals of gastroenterological surgery, 2017)
Purpose The impact of postoperative complications on survival after radical surgery for esophageal, gastric, and colorectal cancers remains controversial. We conducted a systematic review of recent publications to examine the effect of postoperative complications on oncological outcome. Methods A literature search of PubMed/MEDLINE was performed using the keywords “esophageal cancer,” “gastric cancer,” and “colorectal cancer,” obtaining 27 reports published online up until the end of April 2016. Articles focusing on (i) postoperative morbidity and oncological outcome; and (ii) body mass index (BMI), postoperative morbidity, and oncological outcome, were selected. Univariate and multivariate analyses (Cox proportional hazards model) were performed. Results Patients with postoperative complications had significantly poorer long‐term survival than those without complications. Complications were associated with impaired oncological outcomes. The hazard ratios for overall survival were 1.67 (95% confidence interval [CI], 1.31‐2.12), 1.59 (95% CI, 1.13‐2.24), and 1.55 (95% CI, 1.28‐1.87) in esophageal, gastric, and colorectal cancers, respectively. High BMI was associated with postoperative morbidity rate but not with poor oncological outcome. Low BMI was significantly associated with inferior oncological outcome. Conclusions Complications after radical surgery for esophageal, gastric, and colorectal cancers are associated with patient prognosis. Avoiding such complications might improve the outcomes. A systematic review of the impact of postoperative complications on long‐term survival of patients with gastrointestinal cancers showed that infectious complications, particularly pneumonia, were significant risk factors with negative impacts on patient survival.